2007
DOI: 10.1002/jnr.21446
|View full text |Cite
|
Sign up to set email alerts
|

N‐methyl‐D‐aspartate autoreceptors respond to low and high agonist concentrations by facilitating, respectively, exocytosis and carrier‐mediated release of glutamate in rat hippocampus

Abstract: Presynaptic NMDA autoreceptors regulating glutamate release have rarely been investigated. High-micromolar N-methyl-D-aspartate (NMDA) was reported to elicit glutamate release from hippocampal synaptosomes in a Ca(2+)-independent manner by reversal of excitatory amino acid transporters. The aim of this work was to characterize excitatory amino acid release evoked by low-micromolar NMDA from glutamatergic axon terminals. Purified rat hippocampal synaptosomes were prelabelled with [(3)H]D-aspartate ([(3)H]D-ASP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…Consequently, the increase of the spontaneous spiking rate observed during perilymphatic perfusion of salicylate in vivo may partially be attributable to an activation of NMDA autoreceptors on the IHCs, which in turn would increase Glu release, as described previously in the CNS (Berretta and Jones, 1996;Breukel et al, 1998;Woodhall et al, 2001;Yang et al, 2006;Luccini et al, 2007). However, the excitatory effect of NaSal in the presence of GYKI 53784, which completely inhibits AMPA receptors (Ruel et al, 2000), argues against an activation of IHC NMDA autoreceptors as a unique mechanism of NaSal action.…”
Section: Salicylate Modulates Nmda Receptor Responsesmentioning
confidence: 64%
“…Consequently, the increase of the spontaneous spiking rate observed during perilymphatic perfusion of salicylate in vivo may partially be attributable to an activation of NMDA autoreceptors on the IHCs, which in turn would increase Glu release, as described previously in the CNS (Berretta and Jones, 1996;Breukel et al, 1998;Woodhall et al, 2001;Yang et al, 2006;Luccini et al, 2007). However, the excitatory effect of NaSal in the presence of GYKI 53784, which completely inhibits AMPA receptors (Ruel et al, 2000), argues against an activation of IHC NMDA autoreceptors as a unique mechanism of NaSal action.…”
Section: Salicylate Modulates Nmda Receptor Responsesmentioning
confidence: 64%
“…The radiactive tracer allows to measure glutamate exocytosis from isolated nerve terminals avoiding the problems related to the enzymatic degradation of glutamate2425. From here on, throughout the manuscript, the release of preloaded [3H]D-ASP will be referred to as glutamate release.…”
Section: Resultsmentioning
confidence: 99%
“…It is lower though, than after in vivo application of KYNA precursor, L-kynurenine together with probenecid, reported to increase brain KYNA several-fold (Miranda et al 1997;Shepard et al 2003). Yet, having in mind that already nanomolar levels of KYNA block a7 nicotinic receptors and reduce the presynaptic release of glutamate (Carpenedo et al 2001;Hilmas et al 2001;Luccini et al 2007), found enhancement of KYNA synthesis evoked by BHB seems to be clinically relevant, especially as regards potential neuroprotective effects of ketone bodies.…”
Section: Discussionmentioning
confidence: 96%
“…However, recent discoveries have reinforced the hypothesis suggesting an important role of KYNA in brain physiology and pathology. It was demonstrated that high nanomolar levels of KYNA are sufficient to block noncompetitively a7 nicotinic receptors or to increase the expression of a4b2 nicotinic receptors, whereas low nanomolar amounts of compound reduce the presynaptic release of glutamate (Carpenedo et al 2001;Hilmas et al 2001;Luccini et al 2007).…”
Section: Introductionmentioning
confidence: 99%